2017
DOI: 10.1111/dom.13030
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia among patients with type 2 diabetes requiring emergency hospital admission: The Hypoglycaemia In Portugal Observational Study–Emergency Room (HIPOSER)

Abstract: Aims: To analyse the prevalence of severe hypoglycaemia in patients with type 2 diabetes (T2DM) treated with antihyperglycaemic agents (AHA) and requiring emergency room (ER) assistance, and to analyse the prevalence according to type of AHA therapy.Methods: The present study, the Hypoglycaemia In Portugal Observational Study-Emergency Room (HIPOS-ER), was a cross-sectional, observational, multicentre, nationwide study, with specific hypoglycaemia source data collection.Results: Within the study period, a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
0
15
0
2
Order By: Relevance
“…One meta‐analysis showed that severe hypoglycaemia requiring hospital admission was recorded in only 6.7% of all hypoglycaemic episodes 8 . Similarly, the Hypoglycaemia in Portugal Observational Study–Emergency Room (HIPOS–ER), a nationwide observational study of patients with T2DM and hypoglycaemia in the emergency department, showed that 44% of 238 patients required hospital admission 9 . This reflects the variation in management strategies among different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…One meta‐analysis showed that severe hypoglycaemia requiring hospital admission was recorded in only 6.7% of all hypoglycaemic episodes 8 . Similarly, the Hypoglycaemia in Portugal Observational Study–Emergency Room (HIPOS–ER), a nationwide observational study of patients with T2DM and hypoglycaemia in the emergency department, showed that 44% of 238 patients required hospital admission 9 . This reflects the variation in management strategies among different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Absenteeism was considered from ER admission, hospital and home stay post-discharge for both patients and caregivers, as patients with DM are mostly retired and require the assistance of family members [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…HypoglycemIa in POrtugal Study (HIPOS) was a sequence of three observational studies to capture the overall panorama of hypoglycemia events in Portugal in different settings of healthcare assistance: ambulatory (HIPOS-PHARMA) [ 16 ], emergency room (HIPOS-ER) [ 17 ], and hospitalizations (HIPOS-WARD). Their main objective was to assess the clinical characteristics of patients with DM enrolled by type of admission, and the resource consumption and corresponding costs were estimated as secondary objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Para compreender melhor o impacto clínico e económico dos episódios de hipoglicemia grave, associados ao tratamento da DM, foram conduzidos uma série de estudos observacionais transversais multicêntricos em Portugal (Programa HIPOS, Hypoglycemia In Portugal Observational Study). Esta série foi conduzida em três contextos de cuidados médicos, nomeadamente, em ambulatório (HIPOS-PHARMA), 16 na urgência (HIPOS-ER), 17,18 e em internamento hospitalar (HIPOS-WARD). 19 Não obstante o objetivo primário epidemiológico destes estudos, foi realizada uma análise económica secundária a partir da metodologia de microcusteio.…”
unclassified
“…Destacamos ainda a elevada taxa de hospitalizações após ida à urgência (44,1%). 17 Neste estudo, apresentamos os resultados da análise económica combinada dos estudos HIPOS-ER 18 e HIPOS-WARD, 19 com o objetivo de mostrar o impacto económico total expectável durante o controlo de episódios de hipoglicemia grave que requerem internamento, considerando o circuito desde a ida à urgência até alta após internamento hospitalar.…”
unclassified